Achieving Ferroelectricity in a Centrosymmetric High‐Performance Semiconductor by Strain Engineering - Wu, Mengqi; Lou, Zhefeng; Dai, Chen‐Min; Wang, Tao; Wang, Jiaqi; Zhu, Ziye; Xu, Zhuokai; Sun, Tulai; Li, Wenbin; Zheng, Xiaorui; Lin, Xiao (Advanced materials (Weinheim), 2023)
Phase engineering by strain in 2D semiconductors is of great importance for a variety of applications. Here, a study of the strain‐induced ferroelectric (FE) transition in bismuth oxyselenide (Bi2O2Se) films, a high‐performance (HP) semiconductor for next‐generation electronics, is presented. Bi2O2Se is not FE at ambient pressure. At a loading force of ≳400 nN, the piezoelectric force responses exhibit butterfly loops in magnitude and 180° phase switching. By carefully ruling out extrinsic factors, these features are attributed to a transition to the FE phase. The transition is further supported by the appearance of a sharp peak in optical second‐harmonic generation under uniaxial strain. In general, solids with paraelectrics at ambient pressure and FE under strain are rare. The FE transition is discussed using first‐principles calculations and theoretical simulations. The switching of FE polarization acts as a knob for Schottky barrier engineering at contacts and serves as the basis for a memristor with a huge on/off current ratio of 106. This work adds a new degree of freedom to HP electronic/optoelectronic semiconductors, and the integration of FE and HP semiconductivity paves the way for many exciting functionalities, including HP neuromorphic computing and bulk piezophotovoltaics. In a high‐performance semiconductor Bi2O2Se, a strain‐induced ferroelectric transition is demonstrated by the appearance of butterfly loops and 180° phase switching in the piezoelectric force microscopy measurements, together with the evolution of optical second‐harmonic generation. Materials with paraelectrics at ambient pressure and ferroelectrics under strain are rare.